2016
DOI: 10.5603/ep.a2016.0036
|View full text |Cite
|
Sign up to set email alerts
|

Czy galektyna-3 ma związek z nerkowym wydalaniem albumin w cukrzycy typu 2?

Abstract: Introduction: The relation of galectin-3 and diabetes mellitus or renal function have recently

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…Tan et al as well revealed that serum galectin-3 levels were significantly correlated with age, eGFR, urine ACR, and HbA1c, but no correlation was seen with BMI, duration of diabetes, or SBP 24. Far from our results, Yücel et al concluded that no relation was between galectin-3 and the parameters of DM, such as duration of DM, HbA1c, or FPG 28…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Tan et al as well revealed that serum galectin-3 levels were significantly correlated with age, eGFR, urine ACR, and HbA1c, but no correlation was seen with BMI, duration of diabetes, or SBP 24. Far from our results, Yücel et al concluded that no relation was between galectin-3 and the parameters of DM, such as duration of DM, HbA1c, or FPG 28…”
Section: Discussioncontrasting
confidence: 75%
“…In accordance with our results, a large cohort study performed by Tan et al showed that galectin-3 was independently associated with progression of DN (eg, macroalbuminuria), deterioration of renal function (eg, doubling of serum creatinine), as well as initiation of renal replacement therapy after a mean follow-up of 9 years 24. On the other hand, Yücel et al concluded that serum galectin-3 values had no relation to the levels of urinary albumin excretion in patients with DM 28…”
Section: Discussionmentioning
confidence: 99%
“…Since Gal-3 is a DN biomarker that is highly expressed in the serum 29,30 , we detected the expression of Gal-3 in DN in vivo and in vitro. Immunohistochemistry (Fig.…”
Section: Resultsmentioning
confidence: 99%